Mengidentifikasi Kesulitan Belajar Siswa pada Pelajaran Biologi secara Daring di SMAN 13 Takalar - Yasma Yasma; Andi Faridah Arsal; Muhiddin Palennari (Biology Teaching and Learning, 2022)
ABSTRACTThis study aims to determine the profile of student learning difficulties and factors that affect student learning difficulties in online biology lessons at SMAN 13 Takalar. The research method uses a quantitative descriptive approach. The data collection technique is in the form of a questionnaire of student responses related to learning difficulties in biology lessons in online learning at SMAN 13 Takalar. The results of the descriptive analysis of the study showed that the profile of student learning difficulties in online biology lessons at SMAN 13 Takalar, namely mastery of student material is classified as a low category, student learning time is classified as a low category, student learning achievement achievement is classified as a medium category, student focus is classified as a medium category, student enthusiasm is classified as a medium category, student learning behavior is classified as a medium category and the use of online learning applications is classified as a medium category. Keywords: Learning difficulties, online learning, SMAN 13 Takalar.